2020
DOI: 10.1021/acs.jpclett.0c01873
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fluorophores Self-Organize into C-Dot Seeds and Incorporate into C-Dot Structures

Abstract: Various molecular fluorophores have been identified to be present during carbon-dot (C-dot) syntheses. However, the organization of such fluorophores in C-dots is still unknown. We study the self-assembly of 5-oxo-1,2,3,5-tetrahydroimidazo-[1,2-α]-pyridine-7-carboxylic acid (IPCA), a molecular fluorophore present during the synthesis of C-dots from citric acid and ethylenediamine. Both forms of IPCA (neutral and anionic) show a tendency to self-assemble into stacked systems, forming seeds of C-dots during thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…S12 B). Similar results were also derived by Langer et al 36 from their theoretical studies on citric acid based CNDs.…”
Section: Resultssupporting
confidence: 89%
“…S12 B). Similar results were also derived by Langer et al 36 from their theoretical studies on citric acid based CNDs.…”
Section: Resultssupporting
confidence: 89%
“…Recently, self-assembly of a molecular uorophore, namely 5-oxo-1,2,3,5-tetrahydroimidazo-[1,2-a]-pyridine-7carboxylic acid (IPCA), has been shown to form an organized stacked blue emissive CND like structure. 53 It is interesting to point out here that, although the QY of red emission is much lower ($9.1%) than the blue emission ($54.7%), the emission spectral behavior and the QY of the as-synthesized crude sample is largely dictated by the large amount of the red emissive uorophore ($80%) present in the synthesis mixture in comparison to the very small amount of the blue component ($7%).…”
Section: Purication and Characterization Of The Components Of The Cnd Solutionmentioning
confidence: 77%
“…22,23 Molecular dynamics (MD) simulations of noncovalent coassembly of IPCAs and CD fragments revealed that the MF molecules were not only stacked on solvent- exposed aromatic carbons of CDs but also incorporated into the CDs' structure. 15 The PL of CA-based CDs may therefore depend strongly on changes in the electronic structure of MFs induced by interactions with the local environment within the CD as well as interactions between luminescent centers. The diameters of complete CD/MF systems are typically around 2.8 nm, making them too large to be studied using highly accurate quantum mechanical (QM) methods.…”
Section: Introductionmentioning
confidence: 99%
“…3 Here, we study the PL of a CD-embedded IPCA molecules using a computationally affordable hybrid quantum mechanical/ molecular mechanical (QM/MM) 24,25 approach together with reliable CD structural models obtained from MD simulations probing the self-assembly of MFs and CD fragments. 15 Our QM/MM approach applying density functional theory (DFT) to describe the QM region was carefully benchmarked against more accurate theoretical approaches as well as experimental data on hydrated IPCA molecule. After being validated in this way, it was used to calculate the excitation and emission spectra of IPCA in various structural configurations within CD models.…”
Section: Introductionmentioning
confidence: 99%